Genome Reference Assembly for Bottlenecked Southern Australian Koalas. (21st December 2022) - Blanchard, Adam Mark; Emes, Richard David; Greenwood, Alex David; Holmes, Nadine; Loose, Matthew William; McEwen, Gail Katherine; Meers, Joanne; Speight, Natasha; Tarlinton, Rachael Eugenie
Abstract: Koala populations show marked differences in inbreeding levels and in the presence or absence of the endogenous Koala retrovirus (KoRV). These genetic differences among populations may lead to severe disease impacts threatening koala population viability. In addition, the recent colonization of the koala genome by KoRV provides a unique opportunity to study the process of retroviral adaptation to vertebrate genomes and the impact this has on speciation, genome structure, and function. The genome build described here is from an animal from the bottlenecked Southern population free of endogenous and exogenous KoRV. It provides a more contiguous genome build than the previous koala reference derived from an animal from a more outbred Northern population and is the first koala genome from a KoRV polymerase–free animal.